Prevalence of Periodontal Disease Among Coal Mine Workers in Tamilnadu: Life Sciences-Health - B. Na, Dr Vinoth Kumar; R, Dr. Saravana Kumar; B, Dr. Pratebha; Muthu, Dr Jananni; K, Dr. Srinivasan (International Journal of Life Science and Pharma Research, 2022)
Coal miners are predisposed to poor oral hygiene and the resulting dental diseases. we planned to investigate the factors that contribute to the prevalence and severity of periodontal disease among Tamil Nadu coal mine workers. 1500 coal mine workers over the age of 18 were enrolled. A proforma was used to record information about socioeconomic status and habits, followed by a clinical examination that included periodontal parameters such as probing pocket depth (PPD), clinical attachment level (CAL), number of missing teeth, and periodontal screening and recording index (PSR). The study population was divided into three age groups. On analyzing the influence of age on the periodontal health, of the participants, PPD, PSR, and the number of missing teeth were found to be higher in the age group of 51-60 years and CAL was found to be higher in the age group of 41-50 years. Also, the periodontal health of the subjects was influenced by their tobacco usage. The PPD and PSR was found to be higher among past smokers than current users of smokeless tobacco. The number of missing teeth was found to be higher among current users of the smokeless form and clinical attachment level was found to be higher among current users of both forms of tobacco. Our findings indicate that periodontal disease was more prevalent among coal mine workers in Tamil Nadu than in the general population. This highlights the importance of including oral health education and tobacco cessation programs to educate workers on the importance of periodontal health and treatment.